An efficient radio frequency channel distribution in 5g heterogeneous cellular networks for avoiding cross-tier interference in macro and small cells - Qaddus Ahmed; Hassan Shahzad; Minhas Abid Ali (Electrical, Control and Communication Engineering)
Recently, the need for user data rate traffic has increased for running high-bandwidth applications. Therefore, the way forward lies in 5G heterogeneous cellular networks. The 5G network is comprised of two network hierarchies. As the first hierarchy, there are MBSs with large macro cells for macro users. As the second hierarchy, there are FBSs referred to as small cells for femto users. The 5G networks encourage the use of large macro and small cells for efficient utilisation and distribution of channel resources. In this study, the authors have proposed an efficient RF channel distribution mechanism on the basis of the current SINR levels of FUEs and MUEs. On the basis of the users’ present SINR levels, the channels will be allocated by the central MBS to MUEs and FUEs via FBSs. The major obstacle in RF channel allocation to FUEs and MUEs is cross-tier interference at the downlink channel at the MUEs and FUEs from the transmitted signals of MBSs and FBSs. In this study, an efficient RF channel allocation scheme is proposed on the basis of channel modelling constraints, which will minimise the cross-tier interference at the downlink channel at the MUEs and FUEs during RF channel allocation to FUEs and MUEs present in the same coverage area